Comparison of compressive strength and stress - strain behavior of the various components of the Guadalupe Tuff Formation - Sta. Rosa, David Dennis V.
Countless structures have been and are being built on the Guadalupe Tuff Formation (GTF), but despite its long construction history, detailed studies on its strength and deformation behavior is still limited. This leads to conservative calculations and eventually to overdesigned foundation of structures. The components of GTF is proposed to be classified under four (4) general categories: ( 1) Tuff - various volcanic infill, (2) Tuffaceous Sandstone - sand-sized and well-graded, (3) Fluvial Sandstone -sand-sized and poorly-graded (uniform particle size), and (4) Cohesive Soft Rock - silt and clay particles. Samples per classification are subjected to unconfined compression test, prepared under three conditions: (a) Dry -zero moisture content (b) Wet -fully-saturated (c) Cycle -5 cycles of wetting and drying. The unconfined compressive strength and elastic modulus are determined and statistically analyzed. Results show that the proposed classification groups have distinct characteristics. It also reveals that the difference between Dry and Wet conditions are highly significant. Engineers must use the appropriate reference data in conjunction with actual field conditions, whether the GTF is dry or saturated with water.